1987
DOI: 10.1200/jco.1987.5.2.178
|View full text |Cite
|
Sign up to set email alerts
|

High-dose induction chemotherapy of metastatic breast cancer in protected environment: a prospective randomized study.

Abstract: To test the hypothesis of whether high doses of chemotherapy in combination achieve higher response rates and longer durations of response and survival, we treated 33 pre- and perimenopausal patients with good performance status in a prospective trial with escalating doses of fluorouracil, doxorubicin and cyclophosphamide (FAC). Patients were randomly assigned to be treated within a protected environment (laminar air flow room), with prophylactic antibiotics, or in a standard hospital room. Important patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The dose and schedule of doxorubicin were adopted from a pilot study performed by Jones et al [8], in which response rates compared favorably to those reported for conventional doxorubicin-based combination chemotherapies for metastatic breast cancer [9] and are very similar to those reported by Hortobagyi et al using maximally tolerated inpatient CAF [10].…”
Section: Introductionmentioning
confidence: 90%
“…The dose and schedule of doxorubicin were adopted from a pilot study performed by Jones et al [8], in which response rates compared favorably to those reported for conventional doxorubicin-based combination chemotherapies for metastatic breast cancer [9] and are very similar to those reported by Hortobagyi et al using maximally tolerated inpatient CAF [10].…”
Section: Introductionmentioning
confidence: 90%
“…Hyrniuk and Bush (1984) in a retrospective analysis suggested that improvements in the treatment of advanced breast cancer may result from delivery of more dose intense therapy. Patients randomised to dose escalation and protected environment using chemotherapy with 5-fluorouracil, doxorubicin and cyclophosphamide (FAC) failed to demonstrate an advantage for more intense therapy (Hortobagyi et al, 1987). However, in that study a relatively narrow dose intensity range was achieved…”
Section: Discussionmentioning
confidence: 92%
“…In most cases, the slope of the curve is shallow. The study by Tannock [19] [17] o Carmo-Pereira [20] Smalley [18] • Malik [21] 0 Tannock [19] • Hortobagyi [22] % Patient survival Figure 2. also showed an improved quality of life for those patients receiving a higher dose.…”
Section: Evidence That Dose Response Is Important In Therapy Of Breasmentioning
confidence: 99%
“…There have been several randomized trials to date that included differences in dose intensity, although few were designed specifically to answer questions of dose intensity [17][18][19][20][21][22]. These are graphically summarized in Figure 2.…”
Section: Evidence That Dose Response Is Important In Therapy Of Breasmentioning
confidence: 99%